"Am I Going to Be in Trouble for What I'm Doing?": Providing Contraceptive Care in Religious Health Care Systems. Issue 4 (4th December 2019) - Liu, Yuan; Hebert, Luciana E.; Hasselbacher, Lee A.; Stulberg, Debra B.
Abstract : CONTEXT: Catholic systems control a growing share of health care in the United States. Because patients seeking contraceptives in Catholic facilities face doctrinal restrictions that may affect access to and quality of care, it is important to understand whether and how providers work within and around institutional policies regarding contraception. METHODS: In 2016–2018, in‐depth interviews were conducted in Illinois with 28 key informants—including providers (obstetrician‐gynecologists, other physicians, nurse‐midwives) and nonclinical professionals (ethicists, administrators, chaplains)—who had experience in secular, Protestant or Catholic health care systems. Interviews addressed multiple aspects of reproductive care and hospital and system policy. A thematic content approach was used to identify themes related to participants' experiences with and perspectives on contraceptive care. RESULTS: While respondents working in secular and Protestant systems reported few limitations on contraceptive care, those working in Catholic systems reported multiple barriers. Providers who had worked in Catholic systems described variable institutional policies and enforcement practices, ranging from verbal admonishments to lease agreements prohibiting contraceptive provision in secular clinics on church‐owned land. Despite these restrictions, patients' needs motivated many providers to utilize work‐arounds; some providers reported having been pressured or directly instructed to document false diagnoses in patients' medical records. Interviewees described how these obstacles burdened patients, especially those with social and financial constraints, and resulted in delayed or lower quality care. CONCLUSIONS: Providers working in Catholic hospitals are limited in their ability to serve women of reproductive age. Work‐arounds intended to circumvent restrictions may inadvertently stigmatize contraception and negatively affect patient care.